2012
DOI: 10.1111/j.1708-8305.2011.00594.x
|View full text |Cite
|
Sign up to set email alerts
|

Health Risks of Travelers With Medical Conditions—A Retrospective Analysis

Abstract: Travelers with medical conditions had a higher risk of obtaining TRD, predominantly gastrointestinal in nature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
1
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 17 publications
1
24
1
2
Order By: Relevance
“…Glucose needs change with changes in physical activity, delays in meals, changes in diet (e.g., unknown carbohydrate values in unfamiliar foods), and physiologic stress which may ultimately lead to needing changes in insulin dose [23][24][25][26]. Additional travel-related issues that need to be considered are co-morbidity control, travelrelated infections, problems carrying injection material through travel security checkpoints, and unanticipated problems with their glucose meters, insulin pumps, or continuous glucose monitors.…”
Section: Discussionmentioning
confidence: 99%
“…Glucose needs change with changes in physical activity, delays in meals, changes in diet (e.g., unknown carbohydrate values in unfamiliar foods), and physiologic stress which may ultimately lead to needing changes in insulin dose [23][24][25][26]. Additional travel-related issues that need to be considered are co-morbidity control, travelrelated infections, problems carrying injection material through travel security checkpoints, and unanticipated problems with their glucose meters, insulin pumps, or continuous glucose monitors.…”
Section: Discussionmentioning
confidence: 99%
“…14,18,19,25 Apparently the character of the trips was different, with more of organized tour groups or business travel. Despite the similarities in mode of travel and destinations of the two groups in this study, a tendency to more caution was observed among those with diabetes: 4% of their trips to developing countries were organized (vs none of healthy controls) and 20% were not backpacking (vs 8% of healthy controls).…”
Section: Discussionmentioning
confidence: 94%
“…Two studies found high risk for travel-related diseases among those with diabetes. 14,18 However, a prospective study with a matched control group found that T1DM patients traveling to developing countries do not have symptomatic infectious diseases more often or for a longer duration than do travelers without diabetes. 19 Recommendations for travelers with diabetes that have been detailed in the literature include receiving a diabetes-specific checkup prior to the trip, increasing glucose monitoring during the trip and adjusting insulin doses accordingly, and maintaining adequate levels of hydration and nutrition.…”
Section: Discussionmentioning
confidence: 97%
“…The incidence of illness among those travelling to the tropics varies from 15% to 70% in adults and 61% to 85% in children 1–3. This incidence is even higher among adults with chronic health disorders (CHDs), resulting in both an increased risk of infection and a high proportion of problems related to chronic conditions 4 5. However, data regarding health problems among children with CHDs travelling abroad are limited 6 7…”
Section: Introductionmentioning
confidence: 99%